With this pledge [large type] : a Carnton novel - Alexander, Tamera (Alexander, Tamera. Carnton novel., 2019)
What can a woman--a mere governess--do against the scourge of slavery? Elizabeth "Lizzie" Clouston's quietly held principles oppose those of the Southern Cause--but when forty thousand soldiers converge on the fields of Franklin, Tennessee, the war demands an answer. The Carnton home where she is governess is converted into a Confederate field hospital, and Lizzie is called upon to assist the military doctor with surgeries that determine life or death.